Rotor vibration unbalance compensation control of a bearingless induction motor. (11th June 2021) - Yang, Zebin; Jia, Peijie; Sun, Xiaodong; Mei, Haitao
Summary: To handle the unbalanced vibration caused by the centroid deviation in a bearingless induction motor (BL‐IM), a dynamic unbalanced compensation strategy is proposed. Based on the traditional minimum force suppression, the best compensation value can be searched by combining with coordinate system algorithm. Firstly, the generating principle of radial suspension force and the mechanism of rotor vibration are analyzed. Then the mathematical model of dynamic imbalance compensation signal is established. Secondly, a preset compensation signal is applied to the suspension winding. The effective compensation signal that can reduce the rotor displacement is determined by measuring and calculating the corresponding variation in the rotor displacement. The effective compensation value is input into the adaptive iterative algorithm to keep approaching to the optimal compensation value. In addition, the coordinate search algorithm is used to ensure the speed and accuracy of the compensation signal calculation in the time‐varying system, which can realize the effective suppression of rotor vibration. Finally, the compensation control method is simulated in Matlab/Simulink toolbox and tested on a prototype designed by our research group. Both simulation and experimental results show that the time of motor reaching steady state is obviously shortened, and the radial deviation of the rotor is reduced during the operation of the motor. The unbalanced compensation method can effectively and quickly suppress rotor vibration. Abstract : A bearingless induction motor (BL‐IM) contains suspension part and torque part. In the torque part, the rotor is rotated stably by air gap directional magnetic field control. To handle the unbalanced vibration caused by the centroid deviation in suspension part, a dynamic unbalanced compensation strategy is proposed. Firstly, the fundamental frequency displacement signal which makes the rotor vibrate is extracted from the displacement signal in displacement tracking calculation. And the corresponding compensation signal is calculated by the PD iterative algorithm. In addition, the calculation speed of the unbalance compensation signal is accelerated by combining the coordinate system search algorithm in dynamic unbalance compensation control part. The combination can realize the rapid and effective suppression of rotor vibration.